2002
DOI: 10.1080/000155502762064520
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietin Influences Revascularization and Healing in a Rat Model of Random Ischaemic Flaps

Abstract: In order to ascertain whether erythropoietin plays a role in early and late repair processes following ischaemic skin flap injury, a dorsal, caudally based skin flap was created in rats. The rats were successively divided into four groups. Group 1 was not treated. The other groups were treated with a subcutaneous administration of 0.9% NaCl saline solution (group 2), a subcutaneous administration of vehicle (group 3) or a subcutaneous administration of 300 IU/kg/day of recombinant human erythropoietin (group 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 29 publications
4
57
1
2
Order By: Relevance
“…Among these pleiotropic effects, EPO accelerates wound healing and modulates cognitive function. For example, EPO has been observed to promote incisional wound closure in rodent models by reducing ischemic and reperfusion injury, mobilizing endothelial progenitor cells, augmenting angiogenesis, and decreasing inflammation (35). To determine whether pHBSP could also provide benefits in wound healing, we examined its effect in the healing of punch biopsy wounds.…”
Section: Resultsmentioning
confidence: 99%
“…Among these pleiotropic effects, EPO accelerates wound healing and modulates cognitive function. For example, EPO has been observed to promote incisional wound closure in rodent models by reducing ischemic and reperfusion injury, mobilizing endothelial progenitor cells, augmenting angiogenesis, and decreasing inflammation (35). To determine whether pHBSP could also provide benefits in wound healing, we examined its effect in the healing of punch biopsy wounds.…”
Section: Resultsmentioning
confidence: 99%
“…73 The skin has also been shown to be protected by EPO in rodent flap models. 76,77 In these studies, the tissue-protective effects appear to depend strongly on the dose and treatment duration, suggesting that tissues may vary in their responses to EPO.…”
Section: Epo Signaling In Nervous System Cellsmentioning
confidence: 95%
“…Among the pleiotropic effects of EPO reported, a number of investigators have reported significant activity of EPO in promoting the healing of ischemic raised cutaneous skin flaps (10)(11)(12)(13)(14), ischemiareperfusion in random musculocutaneous flaps (15), incisional wounds (10,13), and in colonic anastomoses (16,17). Additionally, skin thermal burns also have been reported to respond in a beneficial way to EPO (18).…”
Section: Introductionmentioning
confidence: 99%